1978
DOI: 10.1159/000122770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neonatal Androgenization on Serum Gonadotropin Levels of Prepubertal and Adult Male and Female Rats

Abstract: Experiments were designed to study the effect of neonatal androgenization on the FSH and LH levels in prepubertal (16 and 30 days old) and adult (90 days old) male and female rats. Androgenization was performed by injecting the pups with 1 mg of testosterone propionate on the 2nd post-partum day. The results obtained in the female rats showed that androgenization increased FSH levels in rats of 30 days old and 90 days old (adult) without modifying the LH levels. Androgenized rats of 16 days old do not show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
2

Year Published

1979
1979
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
2
4
2
Order By: Relevance
“…2B), rather than more rapidly as one would expect if this trait was masculinized. Similar results have been reported by Moguilevskiet al [28]. This defect in LH responsiveness is not due to an inability of the pituitary to respond to GnRH (fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2B), rather than more rapidly as one would expect if this trait was masculinized. Similar results have been reported by Moguilevskiet al [28]. This defect in LH responsiveness is not due to an inability of the pituitary to respond to GnRH (fig.…”
Section: Discussionsupporting
confidence: 90%
“…This notion is supported by the finding that neo natal treatment of male rats with testosterone [28,32] and female rats with estradiol [16] also impairs hypothalamic pi tuitary function and results in sterility.…”
Section: Discussionmentioning
confidence: 86%
“…In previous papers [8,9] it has been dem onstrated that neonatal androgenization in creases FSH in both male and females rats; these results are confirmed again in this paper. Nevertheless, not only such differences dis appear after castration but also androgenized rats showed lower levels of FSH than the controls in the first few days after gonadectomy.…”
Section: Discussionsupporting
confidence: 90%
“…The tonic or male Gn pattern characteristically shows higher levels of plas ma and pituitary follicle-stimulating hormone (FSH) and serum prolactin [4,5,10]. In pre vious papers [8,9] we demonstrated that the administration of testosterone to male and female rats during the first days of life pro duces an increase in the FSH and prolactin levels in the adult as compared with untreated rats.…”
mentioning
confidence: 96%
“…Neonatal treatment with es tradiol [Aguilar, 1979] or testosterone [Mennin and Gorski, 1975] blocks cyclic LH secre tion in the adult female rat. In both sexes, treatment with androgens shortly after birth leads to an increase in adult basal FSH levels without altering LH secretion [Moguilevski et al, 1978]. The gonadotrophic response to castration is attenuated in neonatally estrogenized female rats [Aguilar, 1979;Vaticdn et al, 1980], Together with disturbances in go nadotrophin secretion, gonadal function changes: in adult females an anovulatory syn drome can be seen after neonatal androgen or estrogen treatment [Barraclough, 1961;Gors ki, 1963] while in neonatally estrogenized males testicular atrophy has been reported [Kind et al, 1963].…”
Section: Introductionmentioning
confidence: 99%